2023
DOI: 10.3390/vaccines11050898
|View full text |Cite
|
Sign up to set email alerts
|

Calcinosis Cutis and Calciphylaxis in Autoimmune Connective Tissue Diseases

Abstract: Calcinosis represents a severe complication of several autoimmune disorders. Soft-tissue calcifications have been classified into five major types: dystrophic, metastatic, idiopathic, iatrogenic, and calciphylaxis. Autoimmune diseases are usually associated with dystrophic calcifications, including calcinosis cutis, occurring in damaged or devitalized tissues in the presence of normal serum levels of calcium and phosphate. In particular, calcinosis cutis has been described in dermatomyositis, polymyositis, juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 167 publications
3
10
0
Order By: Relevance
“…In our study involving 872 patients with immune-mediated rheumatic diseases, calcinosis was observed in 86 individuals (9.7%), aligning with a previously reported prevalence ranging from 8.45% to 19.54% [ 2 , 15 , 26 ]. Calcinosis was more common in SSc, affecting 20% of patients (64/310).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study involving 872 patients with immune-mediated rheumatic diseases, calcinosis was observed in 86 individuals (9.7%), aligning with a previously reported prevalence ranging from 8.45% to 19.54% [ 2 , 15 , 26 ]. Calcinosis was more common in SSc, affecting 20% of patients (64/310).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to Mexican and Canadian cohorts [ 3 , 27 ], our patient population mainly had diffuse cutaneous systemic sclerosis, accounting for 59.37%. The most commonly involved sites were the hands and feet, especially the fingers, consistent with findings in prior studies [ 15 , 28 ]. Additionally, SSc patients often exhibited ulcers (55%), impacting 81% of dcSSc and 56% of lcSSc patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6 Dystrophic calcifications are most commonly seen in patients with autoimmune connective tissue diseases such as SSc, dermatomyositis and SLE. 7 Serum testing for calcium, phosphorus and parathyroid hormone levels usually does not reveal any significant results in patients with dystrophic calcifications. 6 Calcinosis cutis lesions often appear as subcutaneous nodules in individuals with SSc.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there are five different subtypes of soft tissue calcifications based on their causes: metastatic, tumoural, idiopathic, calciphylactic and dystrophic 6 . Dystrophic calcifications are most commonly seen in patients with autoimmune connective tissue diseases such as SSc, dermatomyositis and SLE 7 . Serum testing for calcium, phosphorus and parathyroid hormone levels usually does not reveal any significant results in patients with dystrophic calcifications 6 .…”
Section: Discussionmentioning
confidence: 99%